Male infant with paternal uniparental diploidy mosaicism and a 46, XX/46, XY karyotype. Issue 11 (1st August 2019) - Spier, Isabel; Engels, Hartmut; Stutte, Sonja; Reutter, Heiko; Bartels, Enrika; Matos Meder, Sarah; Begemann, Matthias; Mangold, Elisabeth; Eggermann, Thomas
Abstract: A male patient with mosaic paternal uniparental diploidy (PUD) is presented. After birth, the patient presented with hypoglycemia, hemihypertrophy, umbilical hernia, and hepatomegaly. Afterward pancreatic hypertrophy, liver hemangiomas, and cysts were detected sonographically. At the age of 3.5 months, hepatoblastoma was diagnosed. To investigate suspected Beckwith‐Wiedemann syndrome (BWS), extensive genetic analyses were performed using DNA from chorionic villus sampling, amniocentesis, and peripheral blood lymphocytes (chromosome analysis, methylation‐specific multiplex ligation‐dependent probe amplification assays, microsatellite analyses, and single nucleotide polymorphism array analysis). These analyses led to the detection of mosaic PUD. In peripheral blood lymphocytes, a male cell line (46, XY[27]/46, XX[5]) predominated, suggesting a mixture of uniparental isodisomy and heterodisomy. The genetic analyses suggest that the mosaic PUD status was attributable to fertilization of an oocyte by two sperms, with subsequent triploidy rescue giving rise to haploidy, which in turn was rescued. Notably, in the majority of the 28 mosaic PUD patients reported to date, BWS was initially suspected. Mosaic PUD status is associated with a higher risk for a broad range of malignant and benign tumors than in BWS. As tumors can also occur after childhood surveillance into adolescence is indicated. Mosaic PUD must therefore be considered in patients with suspected BWS.